2020
DOI: 10.48550/arxiv.2003.07288
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Pauli blocking effects in thermalization of relativistic plasma

M. A. Prakapenia,
G. V. Vereshchagin

Abstract: We investigate the effects of Pauli blocking on thermalization process of relativistic plasma by solving relativistic Uehling-Uhlenbeck equations with QED collision integral for all binary and triple processes. With this purpose we consider nonequilibrium initial state of plasma to be strongly degenerate. We found that when electron-positron annihilation is active, initial plasma degeneracy is quickly destroyed. As a result in a wide range of final temperatures ranging from nonrelativistic to mildly relativist… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 28 publications
0
1
0
Order By: Relevance
“…In con- 54,55 . It was shown that effects of plasma degeneracy lead to interesting new phenomena such as Bose condensation of photons 56 , and avalanche thermalization due to Pauli blocking 57 . This paper is structured as follows.…”
Section: Introductionmentioning
confidence: 99%
“…In con- 54,55 . It was shown that effects of plasma degeneracy lead to interesting new phenomena such as Bose condensation of photons 56 , and avalanche thermalization due to Pauli blocking 57 . This paper is structured as follows.…”
Section: Introductionmentioning
confidence: 99%